THE NECESSITY OF UNDERSTANDING NATIONAL IDENTITY IN THE PROCESS OF GLOBALIZATION - Utaev Gayrat Gaybullaevich; Botirov Sarvar Bahrom ugli (Western European Studies, 2025)
Today, the process of globalization is a pressing issue for all countries, including Uzbekistan. This process is rapidly developing and has an irreversible nature. Globalization affects various spheres of social life, including economic, political, social, and cultural fields. While it brings vast opportunities and developmental achievements to humanity, it also generates certain threats. In such circumstances, the issue of understanding national identity is of utmost importance
Keywords: independence; development; Globalization